Interdisciplinary collaboration in a case of scrotal extramammary Paget’s disease - Piros, Éva; Ihász, Judit; Riesz, Péter (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Extramammary Paget’s disease (EMPD) is an infrequent tumour that is characterised by a chronic eczema-like rash around the anogenital region. The most common symptom of extramammary Paget’s disease is mild or intense itching around the lumbar, genital, perineal, or perianal regions. Pain and bleeding may result from potential injuries. The thick plaques can be red, squamous, and rough. The first symptoms are itching and burning from one or more persistent plaques. Due to the rarity of the disease, it is difficult to find a specialist. Differential diagnosis is complicated by the fact that EMPD symptoms can mimic those of other diseases [1]. The diagnostic process should include physical, microscopic, immunohistochemical, and interdisciplinary examinations. EMPD is usually treated surgically by removing the skin lesion [2–4]. In some cases, treatment can be effective, such as photodynamic and imiquimod treatment, radiotherapy, chemotherapy, androgen therapy, and CO2 laser ablation [5–7].